Reinvigorating Growth in Developing Countries : Lessons from Adjustment Policies in Eight Economies - Kochhar, Kalpana; Dicks-Mireaux, Louis; Mecagni, Mauro; Offerdal, Erik. (Washington, D.C. : International Monetary Fund, 1996)
This study examines the links between adjustment policies and growth in a small group of developing countries- Bangladesh, Chile, Ghana, India, Mexico, Morocco, Senegal, and Thailand - during 1970 -93. It provides an overview of the adjustment and growth experience, examines in depth several policy issues of particular interest, and distills the principal policy lessons for the design of adjustment policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet